2021
DOI: 10.3390/polym13234239
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance and Ductility Index of Concrete Structures Using Advanced Composite Material Strengthening Methods

Abstract: The performance of concrete structures deteriorates over time. Thus, improving their performance using fiber-reinforced polymers (FRPs), PS strands, and various strengthening methods is important. Reinforced concrete (RC) and prestressed concrete (PSC) structures develop initial cracks in concrete during bending tests, and destruction occurs over a certain period of time after a certain load is generated, and then after the reinforcements and strands yield. However, in the case of FRP structures, after an init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The ductility nature of this UHPC beams was also revealed in the slow (and not sudden) increase in the width of the beams' existing cracks after yielding of the tensile steel reinforcements. The ductility reduction of about 48% in the UHPC beam without stirrups can be attributed to the absence of shear reinforcement in the beam; however, it has better ductility when compared with the ductility indices of some studies conducted on high performance concrete and reinforced concrete [45,46,44). Further analysis showed that there was 2.6% difference in the ductility index of the experimental beam with stirrups and the numerically simulated beam with stirrups and steel fibers, while 8.3% difference existed between that of the experimental beam with stirrups and the numerically simulated beam with stirrups but without steel fibers.…”
Section: Ductility Evaluation Of the Uhpc Beamsmentioning
confidence: 88%
“…The ductility nature of this UHPC beams was also revealed in the slow (and not sudden) increase in the width of the beams' existing cracks after yielding of the tensile steel reinforcements. The ductility reduction of about 48% in the UHPC beam without stirrups can be attributed to the absence of shear reinforcement in the beam; however, it has better ductility when compared with the ductility indices of some studies conducted on high performance concrete and reinforced concrete [45,46,44). Further analysis showed that there was 2.6% difference in the ductility index of the experimental beam with stirrups and the numerically simulated beam with stirrups and steel fibers, while 8.3% difference existed between that of the experimental beam with stirrups and the numerically simulated beam with stirrups but without steel fibers.…”
Section: Ductility Evaluation Of the Uhpc Beamsmentioning
confidence: 88%
“…also affects energy dissipation. Roche et al [58] When evaluating the structures' flexural behavior, it was found that both the factors of volume fraction Vf and the type of structure contribute to the results [59], and the combination of these factors makes it impossible to observe any unequivocal regularities in behavior trends in the assessment of ductility. Based on the obtained ductility indices, it can be concluded that the Rhombus structure appears to be the best in terms of ductility; however, the structure showed the lowest values of bending stresses.…”
Section: Energy Absorption and Ductility Assesmentmentioning
confidence: 99%
“…The ductility index, µ E , represents the quotient of the total and elastic energy, and it is expressed by Equation ( 9) [50,51]:…”
Section: Energy Absorption and Ductility Assesmentmentioning
confidence: 99%